Enteric viruses exploit the microbiota to promote infection - Robinson, Christopher M. (Curr Opin Virol, 2019)
Enteric viruses infect the mammalian gastrointestinal tract which is home to a diverse community of intestinal bacteria. Accumulating evidence suggests that certain enteric viruses utilize these bacteria to promote infection. While this is not surprising considering their proximity, multiple viruses from different viral families have been shown to bind directly to bacteria or bacterial components to aid in viral replication, pathogenesis, and transmission. These data suggest that the concept of a single virus infecting a single cell, independent of the environment, needs to be reevaluated. In this review, I will discuss the current knowledge of enteric virus-bacterial interactions and discuss the implications for viral pathogenesis and transmission.